Internalization of Human Values in Physics Learning through a Love-Based Curriculum to Build Environmentally Caring Character - Nurhikma Syam; Heru Kuswanto; Yusman Wiyatmo (Journal of Educational Sciences, 2026)
The global environmental crisis demands a fundamental transformation in science education, shifting from mere cognitive knowledge transfer to a medium for holistic character formation. This conceptual article examines the urgency of internalizing human values such as empathy, compassion, and justice into physics learning. The author proposes a "Love-Based Curriculum" as a transformative pedagogical framework to bridge the gap between abstract physics concepts and the development of environmentally caring character. This article is developed using a Systematic Literature Review (SLR) approach. Data collection was conducted by examining various credible and relevant references to obtain a comprehensive understanding of the topic. The article synthesizes various approaches, ranging from compassionate pedagogy to the integration of sustainability issues (such as climate change and waste management) into the physics curriculum. The findings indicate that a humanistic approach not only improves cognitive learning outcomes but also significantly fosters ecological awareness, environmental literacy, and students’ motivation to become agents of change. The Love-Based Curriculum is argued to be a strategic intervention to ensure more equitable, inclusive, and relevant physics learning that addresses future challenges.